PERSEPSI WISATAWAN DOMESTIK MENGENAI EKOWISATA DI WANA WISATA KAWAH PUTIH - Fahrurozy Darmawan (Fakultas Pariwisata Universitas Pancasila, 2021)
Wana Wisata Kawah Putih is a natural tourist destination in West Java with the potential of ecotourism being developed and becoming the most demostic tourist attraction. As an ecotourism concept destination, Wana Wisata Kawah Putih should focus on enviromental, development and community welfare. The tour manager needsnto know more about the perception of visiting tourists as assessments in order to be in line with what managers want and what tourists expect. Thus the goal of research is to identify natural attaractions and analyze the domestic tourist perceptions of ecotourism in the Wana Wisata Kawah Putih. The design of the research is to use qualitative methods of data collection that researchers are using to observe, an interview of the administrators of KBM ecotourism who have been to the Wana Wisata Kawah Putih haven with a snowball sampling and a library study. After analyzing data collection through that data using data reduction, collate data and verifying data. Based on the results this study, it could be concluded taht natural tourist atrrations in the Wana Wisata Kawah Putih have already made a number of efforts to maintain environmental ecosystems but haven’t been optimal in the field and i haven’t had access to the tour guide, the interpretation board and the restoration of the tourist area. While the domestic tourist perception of ecotourism in the Wana Wisata Kawah Putih that tourists can feel natural beauty and take a picture but the domestic tourists have less active participation with environment.